A systematic experimental study of parameters influencing 131-iodine in vivo spectroscopic measurements using age-specific thyroid phantoms. (24th April 2018) - Beaumont, Tiffany; Rimlinger, Maeva; Broggio, David; Ideias, Pedro Caldeira; Franck, Didier
Abstract: In case of nuclear accident, the internal exposure monitoring of the population will preferably focus on the detection of 131 I in the thyroid by in vivo monitoring. In most cases, the calibration of in vivo monitoring is performed with an adult thyroid phantom, which raises doubts regarding the relevance of child exposure assessment. In this study, the influence on the calibration of the thyroid volume, the counting distance and the positioning variations are studied experimentally in a systematic way. A NaI and a germanium detector along with a realistic age-specific set of four thyroid phantoms were used to carry out this study. The thyroid phantom volumes correspond to the following ages: 5, 10, 15 and adult. It was found that the counting efficiency varies linearly with the thyroid volumes for both detectors and whatever the phantom–detector distance is. The variation in counting distance strongly influences the measurement. Whatever the thyroid volume, a 30% difference in efficiency was found between the measurement at the contact and 1 cm for the NaI detector. A mathematical model giving the variation of the counting efficiency as a function of phantom–detector distance is provided. The study of positioning uncertainty has shown that the lateral/vertical displacements induce negligible efficiency variations and that it is relatively independent of the thyroid volume. The counting distance is a major parameter, which must be considered to assess the uncertainty of the subjects' measurements. The data reported here might serve to extract useful orders of magnitude when similar detectors are used. For other detectors, a similar trend might be expected and the information provided here could reduce the amount of experimental work needed to obtain it.